Sectarianization, Identity, and How Terrorism Prevails: The Case of Al-Qaeda in the Islamic Maghreb (AQIM) in the Sahel Region of Africa - Adzraa Andira (Kelompok Studi Mahasiswa Pengkaji Masalah Internasional Unpar, 2021)
Various patterns have emerged as a result of globalization when it comes to controlling the kind of threats that a country may face, particularly non-traditional ones. One of them is terrorism, which occurences concentrated in specific places of the world, with North and Sub-Saharan Africa dominating for a variety of reasons. While there are other operational areas contested by various terrorist groups, the Sahel is one of the most well-known, with Al-Qaeda in the Islamic Maghreb (AQIM) being one of the most infamous terrorist groups. Legacies of weak and corrupt governments and institutions, unenforced border security, historical disadvantages, and crippled economies may serve as catalysts for such groups' growing influence, but this paper would argue that the use of sectarianism as a tool of identity mobilization is one of the reasons for AQIM's prevalence as a terrorist group.